É preciso propiciar a aprendizagem de inglês na escola: experiências bem-sucedidas para investir em uma mudança de paradigma - Climene Fernandes Brito Arruda (2014)
This paper presents a narrative study of the successful experiences in learning English of eight students from regular schools in Belo Horizonte, Minas Gerais: four from public schools and four from private schools. The objective of the research is to document and describe successful experiences, especially in a school context, to understand how they are explained, since the usual paradigm is that the teaching of English in schools is inefficient. The study is based on the concept of experience by Miccoli (1997-2013) and the frame of reference of students` language learning experiences proposed by Miccoli & Bambirra (BAMBIRRA, 2009), articulated into several themes: social paradigm (CAPRA, 1996); methodology of narrative research (LIEBLICH ET AL., 1998; CONNELLY & CLANDININ, 2000; BENSON, 2005; ARAGÃO, 2007; BARCELOS, 2006A, 2008; PAIVA, 2008); motivation associated with success on the Sociocultural Theory perspective (OXFORD & SHEARIN, 1994; GARDNER, 2005, 2006; DÖRNYEI, 2001, 2005; DÖRNYEI & USHIODA, 2011), and finally, human agency, in the light of the Sociocultural Theory (AHEARN, 2001; LANTOLF & PAVLENKO, 2001; LANTOLF & THORNE, 2006, VAN LIER, 2008). A quantitative and qualitative approach to the analysis and presentation of the results was adopted. The data were collected using interviews in order to assess students` language proficiency, oral narratives to understand their learning process and also, narratives by their teachers to gain insights on the students success and their working environment. The results show the interrelatedness of English learning in the classroom and non-classroom contexts and document intertwined experiences of cognitive, motivational, conceptual, contextual, social and emotional natures that enable successful student experiences. The role of students agency, related to their motivation, stands out in the data analysis, revealing itself to be aided by the situated context for learning that their teachers provide and by the contextual opportunities (affordances) found outside the classroom and valued by students. The implications of this study for learning English in schools are in understanding the elements that modulate agency and motivation, as well as the situated context, which together contribute to the success of these students and in emphasizing the need to afford English learning in schools.